KAJIAN SEMANTIK PROTOTIPE TERHADAP ISTILAH “DESA WISATA” - Ari Wulandari (Unit Penelitian dan Publikasi Fakultas Ilmu Budaya Universitas Gadjah Mada, 2020)
Every person has a specific idea of a word, term, phrase, or discourse. The thought is heavily influenced by culture background and surroundings. This study uses the term “tourist village” to understand the thinking of society. The objectives of this study are to assess and describe the prototype semantics “tourist village” based on the notion of society. The study was conducted using a questionnaire that has been designed based on the hypothesis derived from field observations regarding the definition of “tourist village”. The questionnaire has given to 50 persons at random. The respondent's answer was counted, and the results were analyzed based on the predetermined variables. The research proves that prototype semantics “tourist village” as a linguistics study has four main variables, namely the beauty of nature, people skills, culture, and the arrival of people. The results of this study concluded that the prototype semantics “tourist village” according to the community is a village that has a natural beauty, people skills are adequate and special, unique culture, and there are people who want to know the arrival of distinctiveness that is owned in the village.